2006
DOI: 10.3384/ijal.1652-8670.061231
|View full text |Cite
|
Sign up to set email alerts
|

Gender and Generational Continuity: Breadwinners, Caregivers and Pension Provision in the UK

Abstract: The UK is considered a 'male breadwinner/female part-time carer' state due to men and women conforming to stereotypical gender roles within partnerships, and welfare policies reflecting and reinforcing this gender division. Using data from the General Household Surveys 2001 and 2002, this article shows that mothers continue to be markedly disadvantaged in participating in the accumulation of pensions compared to women who have never had children. This is mostly because they take on caring roles at the expense … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…The conflict between paid work and caring is likely to intensify in the future. Women's economic activity rate is expected to rise further (Madouros 2006), which is crucial to safeguard women's pensions in the future (Price 2006). Despite rising female labour-market participation rates, current levels of informal care by married couples could be sustained if men increased their care-giving to the same extent as women might reduce it, but paid work also limits men's involvement in informal care.…”
Section: Discussionmentioning
confidence: 99%
“…The conflict between paid work and caring is likely to intensify in the future. Women's economic activity rate is expected to rise further (Madouros 2006), which is crucial to safeguard women's pensions in the future (Price 2006). Despite rising female labour-market participation rates, current levels of informal care by married couples could be sustained if men increased their care-giving to the same extent as women might reduce it, but paid work also limits men's involvement in informal care.…”
Section: Discussionmentioning
confidence: 99%
“…The extant literature examining these two major age-based institutions provides a wealth of examples of how the institutionalized life course contributes to the marginalization and discrimination that, engaging with age, engages also with gender. For example, recent developments within the pension system schemes that promote individualization and privatization of pensions are found to exacerbate gender inequality (Leitner 2001), where the diverse life courses and work histories of men and women have their immediate result in a considerable gender pension gap (Foster and Smetherham 2013;Frericks et al 2007Frericks et al , 2009Price 2006). Therefore, not without a reason, Hartmann and English (2009) stated that financial security while on pension is of particular importance to women.…”
Section: Gendered Ageism As Doingmentioning
confidence: 99%
“…The current income and asset position of pensioners has been well-documented (Banks et al 2010). Research has shown that employment histories (Ginn and Arber 1996), family roles (Evandrou and Glaser 2003) and gendered roles (Arber and Ginn 2004) adversely influence women's financial wellbeing in later life; through interrupted work histories, periods of part-time work, low pay and lack of access to occupational pension provision, especially affecting working-age mothers at all educational levels and women divorcees (Ginn 2003; Ginn and Arber 2002; Ginn and Price 2002; Price 2006 a ). On average, older women have much lower incomes than men in late life and are more likely than men to have incomes below the UK threshold for means testing (Ginn and Price 2002; Glaser et al 2009 a ; Price 2006 b , 2006 c ).…”
Section: Employment and Family Histories: Effects On Later-life Incomementioning
confidence: 99%